A Simplified Method for Determining Blood-to-Plasma Ratios in vitro and ex vivo by Matrix Matching with Blank Blood or Plasma - Zhang, Xiaomei; Jenkins, Gary J.; Desino, Kelly E.; Liu, Jinrong; Larsen, Mary; Stresser, David M. (Drug Metabolism and Bioanalysis Letters, 2023)
Objective: This work describes a simplified, 96-well plate method for determining the blood-to-plasma concentration ratio (BP ratio) for small molecules.Methods: The need for calibration curves was eliminated using a matrix-matching approach in which blood samples were mixed with blank plasma and plasma samples were mixed with blank blood. As a result, both blood- and plasma-origin samples shared an equivalent matrix ahead of bioanalysis. In the in vitro assay, identical sample matrices were achieved by using the same source of blank plasma and blood.Results: In humans, a good correlation (R2 = 0.84) was observed between the data obtained in this matrix-matching method and literature values for 11 commercial compounds possessing a wide range of logD values across multiple chemical classes. In addition, this method showed good agreement with in vitro BP ratios for 10 proprietary compounds determined radiometrically (R2 = 0.72) in human and preclinical species. Finally, the in vitro matrix matching method compared favorably to BP ratios determined ex vivo for 13 proprietary and literature compounds (R2 = 0.87) in rat.Conclusion: This method, suitable for in vitro and ex vivo BP ratio determinations, is operationally efficient, robust, and a useful improvement upon previously published methods.
Keywords: radiometrically